2001
DOI: 10.1074/jbc.m100277200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inhibits the Peroxisome Proliferator-activated Receptor α/ Retinoid X Receptor Gene Regulatory Pathway in Cardiac Myocytes

Abstract: Hypoxia triggers a cascade of cellular energy metabolic responses including a decrease in mitochondrial oxidative flux. To characterize gene regulatory mechanisms by which mitochondrial fatty acid oxidative capacity is diminished in response to hypoxia, cardiac myocytes in culture were exposed to long-chain fatty acids (LCFA) under normoxic or hypoxic conditions. Hypoxia prevented the known LCFA-induced accumulation of mRNA encoding muscle carnitine palmitoyltransferase I (M-CPT I), an enzyme that catalyzes th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
113
0
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 164 publications
(122 citation statements)
references
References 36 publications
4
113
0
5
Order By: Relevance
“…DISCUSSION PPAR␣, a lipid-activated transcription factor, plays a critical role in the control of cellular energy metabolism in a variety of physiologic and pathologic states. Evidence has emerged that PPAR␣ activity is modulated in heart and liver during diverse stress responses, including fasting (1), cardiac hypertrophy (4), and cellular hypoxia (32). This implies that upstream signaling events activated by cellular stressors are linked to changes in PPAR␣ activity, which in turn regulates mitochondrial energy metabolism.…”
Section: P38 Mapk-mediated Activation Of Ppar␣ Maps To Phosphorylatiomentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION PPAR␣, a lipid-activated transcription factor, plays a critical role in the control of cellular energy metabolism in a variety of physiologic and pathologic states. Evidence has emerged that PPAR␣ activity is modulated in heart and liver during diverse stress responses, including fasting (1), cardiac hypertrophy (4), and cellular hypoxia (32). This implies that upstream signaling events activated by cellular stressors are linked to changes in PPAR␣ activity, which in turn regulates mitochondrial energy metabolism.…”
Section: P38 Mapk-mediated Activation Of Ppar␣ Maps To Phosphorylatiomentioning
confidence: 99%
“…Myocytes-To determine whether PPAR␣ is a target for SAPK-mediated phosphorylation in cardiac myocytes, 32 P labeling of adenoviral-expressed, epitope-tagged PPAR␣ in primary cultures of neonatal rat cardiac myocytes was performed under serum-free conditions. Immunoprecipitation of 32 P-labeled FLAG-PPAR␣ demonstrated that PPAR␣ exists as a phosphoprotein under basal culture conditions in cardiac myocytes (Fig.…”
Section: Activation Of Sapk Pathways Leads To Phosphorylation Of Pparmentioning
confidence: 99%
“…The rationale in this case is that glucose utilization requires less oxygen consumption for energy generation than does FAO and does not worsen acidosis in the damaged myocardium the way FAO can. Severe ischemia itself turns off PPAR-␣-regulated gene expression as a source of ATP production from fatty acids (39,65). Glucose transporter GLUT4-deficient mice develop profound myocardial dysfunction during ischemia (89), suggesting the ability to switch to glucose utilization after ischemia is critical (56).…”
Section: Ppar-␣ and The Heartmentioning
confidence: 99%
“…Incubation with oxidized LDL or beta verylow-density lipoprotein can accelerate lipid accumulation in vascular SMC 2) ; however, even high concentrations of native LDL, such as in the order of 5 mg/mL, are not sufficient to induce lipid deposition in vascular SMCs 3) . Arterial wall cells are exposed to various types of stimulants 4) , from growth factors and cytokines to achieved in part by an increase in cellular glycolytic capacity with concomitant down-regulation of mitochondrial fatty acid oxidation 6) . These metabolic changes are thought to be transcriptionally activated by hypoxiainducible factor 1-alpha (HIF-1 ) in a wide variety of cell types and by hypoxia-inducible factor 2 /EPAS1 in vascular endothelial cells 7,8) .…”
Section: Introductionmentioning
confidence: 99%